The Effect of Corruption on Internal Conflict in Iran Using Newspaper Coverage - Mohammad Reza Farzanegan; Reza Zamani (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the effect of a corruption reflection index on internal conflict in Iran using a novel measure of corruption based on newspaper coverage. We use the Vector Autoregression (VAR) model and its applied tools of impulse response and variance decomposition analyses to track the response of protests to shocks in the level of corruption. Using annual data from 1962 to 2019, we find a positive and significant response of protests to a positive shock in the news-based corruption reflection index. We also show that the main channels where higher corruption may lead to higher internal protests are through economic growth and military spending.
Keywords: D73; D74; F52; C54; 330; corruption; protest; conflict; newspaper coverage; Iran; economic growth; revolution